PERSEPSI MASYARAKAT TENTANG LAKI-LAKI BASUNTIANG DALAM ADAT PERKAWINAN DI NAGARI SIMPANG LAMA KECAMATAN PANCUNG SOAL - WATI, MELDA - (Pendidikan Sosiologi, 2014)
Together with tradition of laki-laki basuntiang in marriage tradition at NagariSimpang Lama kecamatan Pancung Soal , seen from the different redization process , thatthis tradition has a difference with Nagari at South Pesisir, at Nagari Simpang Lama themen are use Suntiang as head jewelry at that time of wedding party . As for the questionabout this research is how to realization of Basuntiang , Marapulai perception , andsociety about Laki-Laki Basuntiang .The theory that used in this research is phenomenology theory based on AlfredSchutz. This research approach is qualitative with type descriptive research. technique oftaking source with the way purposive sampling with total of source is 12 persons . Typedata in this research are primary data and secondary data . Data is gathered by interview ,observation and document study with unit of analysis that use is model analysis Miles andHuberman , that consist of four steps are : gathering data , reduction data , presentationdata , and take the conclusion .Based on result of the research that is done, realization process of Basuntiang forMarapulai in marriage tradition at Nagari Simpang Lama is when the bridge groomdelivered to brideâs place ( anak daro ) that have two steps , are the first step is waitingbako , and the second step Manjapuik Marapulai, is the marapulai itself be shy andhomosexual (be a girl) for holding process of Basuntiang. Society perception oboutrealization of basuntiang at Nagari Simpang Lama is a proud of Nagari Simpang Lama .